A taxonomy of pragmatic measures of HIV preexposure prophylaxis use. (1st November 2020) - Pyra, Maria; Rusie, Laura; Castro, Michael; Keglovitz Baker, Kristin; McNulty, Moira; Bohm, Nick; Prokurat, Andrei; Schneider, John
Abstract : Objectives: As delivery of preexposure prophylaxis (PrEP) becomes an HIV prevention priority in the United States, standard, pragmatic measures of PrEP use are needed to compare and evaluate prevention implementation programs. By using readily available electronic health record data, we describe and compare measures of persistence and retention. Design: Retrospective cohort. Methods: Using electronic health record prescription data for patients at a large urban Federally Qualified Health Center from 2015 to 2019, we calculated measures of persistence and retention and compared them to pharmacy claims data, PrEP biomarkers, and HIV outcomes. Results: Total PrEP time was 19.8 months on average. During this period, average adherence by medication prescription ratio (MRxR) was 89%; 77% of patients had an MRxR at least 85% and 90% have an MRxR at least 57%. Over the first 6 months, average proportion of days covered (PDC) at least 85% was 53% and PDC at least 57% was 57%. Prescription fill rates, based on claims data from a pharmacy partner, ranged from 45 to 60%. Using tenofovir-diphosphate as the gold standard, PDC had high sensitivity (97%) but low specificity (⩽13%). As a measure of retention, over the first 6 months, 59% of patients had quarterly HIV tests. Conclusion: Total PrEP time is useful measure of overall persistence, while PDC can assess persistence and adherence at a specific time point. Adherence by PDC is more conservative compared with MRxR; both will overestimate true adherence. Retention in care can be measured by quarterly HIV tests. Using consistent terminology and reporting timepoints and adherence thresholds will help reporting and comparing PrEP delivery programs. Abstract : Supplemental Digital Content is available in the text